Taxonomia de Asterocheridae (Copepoda: Siphonostomatoida) associado a esponjas do litoral brasileiro - Silva, Rodrigo Johnsson Tavares da (1997)
The Brazilian coast has the Siphonostomatoid species that parazitise fishes relatively well known, however there are no records of the Siphonostomatoid species that live associated with invertebrates. Thus, sampling was clone in three diferent areas of the Brazilian coast: Cagarras Islands, Rio de Janeiro (RJ) ; Viçosa Reefs, Nova Viçosa (BA) and Porto de Galinhas (PE), to study these Siphonostomatoids. ln these samples the Asterocheridae species associated with Porifera were analyzed. Nine new species are described, six of them belonging to the genus Asterocheres (A. abrolhensis n. sp., A. crenulatus n. sp., A. lunatus n. sp., A. paraboecki n. sp., A. spinopaulus n. sp. and A. tetrasetosus n. sp.), one to Asteropontoides (A. elephantinus n. sp.), one to Cletopontius (C. titanus n. sp.) and, one to Monocheres (M cagarrensis n. sp.). For the first time a male from the genus Cletopontius is described. Besides these new species a new genus (Kolomyzon n. gen.) of Asterocheridae is described to the species Kolomyzon angustus n. gen. n. sp. Keys for the genera of Asterocheridae and for the species of the studied genera are presented. The genus Asterocheres has a worldwide distribution, but for the first time, it is recorded for the South western Atlantic. Asteropontoides, Cletopontius and Monocheres whose species were only known from the lndian Ocean were also first recorded for the Atlantic Ocean.